Analysis of edge transport in L-mode negative triangularity TCV discharges. (March 2023) - Muscente, P.; Innocente, P.; Ball, J.; Gorno, S.; ,; ,
Highlights: Edge modelling of TCV experiments using SOLEDGE2D-EIRENE code. Investigation of the power exhaust and transport coefficient behaviors of the Negative Triangularity (NT) with respect to the Positive Triangularity (PT) magnetic configuration. Presents the difference in edge transport between PT and NT configurations, showing that NT affects power exhaust behaviour. Abstract: One of the major problems for future tokamak devices are ELMs (Edge Localized Modes) as they can lead to large, uncontrolled heat fluxes at the machine targets. For this reason, different techniques and alternative magnetic configurations are under study to mitigate or avoid these phenomena. One of the most promising among these studies is the Negative Triangularity (NT) configuration, which exhibits a global confinement comparable with H-Mode operation and, staying in L-mode, could enable an easier power exhaust dissipation due to a possible bigger heat flux decay length with respect to the conventional Positive triangularity (PT) H-mode. In this work, the fluid code SOLEDGE2D-EIRENE is used to study edge transport. Studies are made on discharges performed in the TCV device (Tokamak à configuration variable), which can create a variety of different plasma geometries thanks to 16 independently powered poloidal field coils and its open vacuum vessel. In order to understand if and how power and particle exhaust in NT differs with respect to those of the PT shape, four discharges in single null magnetic divertor configuration with fixed lower triangularity (δbot = +0.5) but with different upper triangularity (from δup = −0.28 to δup = +0.45) have been modelled. All of them are ohmically heated, L-mode deuterium plasmas, and in the high recycling regime. Moreover, these discharges were previously used in [4] to measure the heat flux decay length by IRT (Infrared Thermography), allowing us to make comparisons with modelling results.